Content Development: Character-Based Technopreneurship Education for Young Ganesha Entrepreneurs - Kertiasih, Ni Ketut; Setemen, Komang; Permana, Agus Aan Jiwa (Darul Yasin Al Sys, 2024)
These reforms should focus on curriculum updates, graduate competencies, teacher qualifications, funding, and the decentralization of education. One of the key responsibilities of educators is to innovate teaching materials, ensuring they prepare graduates with the necessary technological skills for future careers or entrepreneurship. The introduction of the